Menjaga Kesehatan Mata untuk Penglihatan yang Optimal - Atzmardina, Zita; Dian Hafsari Fitri; Cornelia Kartika Matthew; Anissa Rachavidia; Muhamad Daffa Alfarisi (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
Conjunctivitis is an inflammation of the conjunctiva commonly affecting individuals of all ages. In Indonesia, its rising prevalence raises concerns due to its impact on quality of life and potential for community transmission. This program aimed to improve public awareness and prevention of conjunctivitis, particularly in the Puskesmas area. Cause analysis was conducted using Blum’s Paradigm, with data collected via a mini-survey. Problem prioritization applied the non-scoring Delphi method, and root causes were identified using a fishbone diagram. The intervention focused on health education and proper handwashing demonstrations. Evaluation was conducted using the PDCA (Plan-Do-Check-Act) cycle and a continuous monitoring system. Results showed an increase in post-test scores following education sessions, indicating improved community understanding of proper hand hygiene to prevent conjunctivitis transmission. The initiative is expected to continue as part of community health promotion and prevention efforts.